Performance evaluation of 4-quadrature amplitude modulation over orthogonal frequency division multiplexing system in different fading channels scenarios - Hasan Fadhil Mohammed; Ghanim Abdulkareem Mughir (Institute of Advanced Engineering and Science, 2022)
Orthogonal frequency division multiplexing (OFDM) is a multicarrier modulation (MCM) technique that divides the wide bandwidth into parallel narrow bands, each of which is modulated by orthogonal subcarriers. Currently, OFDM is a high-spectral efficiency modulation technique that is used in a variety of wired and wireless applications. The transmitted signal in a wireless communication channel spreads from transmitter to receiver through multiple reflective paths. This triggers multipath fading, which causes variations in the received signal's amplitude and phase. Slow/fast and frequency-selective/frequency-nonselective are the main types of multipath fading channels. Therefore, in this paper, we proposed new models for modeling multipath fading channels, such as the exponential fading channel and the Gamma fading channel. In addition, new bit-error-rate (BER) derivations have been derived. The performance of the OFDM system over proposed channel models has been evaluated using Monte-Carlo simulation and compared to the Rayleigh fading channel model. The obtained results via simulations show that the exponential fading channel at a rate parameter (λ=0.5) outperforms the Rayleigh fading channel by 6 dB for all values of Eb/No, while the Gamma fading channel at (α=2) outperforms the Rayleigh fading channel by 3 dB for all values of Eb/No.